1963
DOI: 10.1901/jeab.1963.6-163
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF HUNGER AND VI VALUE ON VI PACING1

Abstract: In two experiments, each involving four rats, responses preceded by an inter-response time between 8 and 10 sec in duration were intermittently reinforced. In Experiment I, final performance was compared under two hunger levels, while the frequency of reinforcement was held constant by a VI 5 schedule. In Experiment II, hunger was held constant and VI 3 was compared with VI 8. Both hunger and frequency of reinforcement increased the over-all rate of response, but the exact effects of these operations on tempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

1964
1964
1994
1994

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
6
1
Order By: Relevance
“…In the delayed-reinforcement experiments (Ferster and Hammer, 1965) where rhesus monkeys were introduced to long delays of reinforcement without the required history of successive approximations, the animals lost weight continuously without any corresponding increase in the food-reinforced behavior. These data are in contrast to many classical operant experiments (Clark, 1958;Revusky, 1963;Perin, 1942;Conrad, Sidman, and Herrnstein, 1958) which demonstrated a z I Fig. 3.…”
Section: The Role Of Deprivationcontrasting
confidence: 87%
“…In the delayed-reinforcement experiments (Ferster and Hammer, 1965) where rhesus monkeys were introduced to long delays of reinforcement without the required history of successive approximations, the animals lost weight continuously without any corresponding increase in the food-reinforced behavior. These data are in contrast to many classical operant experiments (Clark, 1958;Revusky, 1963;Perin, 1942;Conrad, Sidman, and Herrnstein, 1958) which demonstrated a z I Fig. 3.…”
Section: The Role Of Deprivationcontrasting
confidence: 87%
“…Finally, it should be noted that the effects of the schedules on Rats 7 to 12 do not appear to be in agreement with an observation by Revusky (1963). He also examined the effects of VI value on behavior generated by response pacing schedules, and concluded that the pacing contingency "did not eliminate the usual effects of .…”
Section: Discussionmentioning
confidence: 83%
“…These variables undoubtedly affect the paced distributions and therefore need to be included in the rationale. Some work has been done (Revusky, 1963) but so far the results have been too inconclusive to suggest any specific modifications or generalizations of the present formulation.…”
mentioning
confidence: 81%